FAKTOR KONVERSI PRODUKSI DOLOK PINUS DARI HUTAN ALAM (Studi kasus di satu perusahaan hutan di Aceh) - Maman Mansyur Idris; Sona Suhartana (Jurnal Penelitian Hasil Hutan, 1995)
This paper is presenting the results of the study on conversion factor of log production of Pine (Pinus merkusii) from natural forest. Study carried out at a logging company in Aceh in 1991. The aim of the study was to know the conversion factor of Pine log production from natural forest including volume and mass units of measurement.The data were analised statistically by t-test. The results of this study showed that the conversion factor of Pine log production unit were : (1) for fresh cut, 1 month and 2 months duration was 0.985 m3/ton or 1.0152 ton/m3, (2)for 3 and 4 months was 1.086 m3/ton or 0.9208 ton/m3 and (3)for 1 year was 1.239 m3/ton or 0.8071 ton/m3.